Surface-treated magnetic material and magnet

By polishing hard magnetic particles, it improves its magnetic coercivity and forms permanent magnets including polishing hard magnetic particles, solving the problems of poor demagnetization and high dependence on rare earth materials at high temperatures, achieving higher anti-demagnetization and lower cost.

CN119724892APending Publication Date: 2025-03-28ABB (SCHWEIZ) AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411330039.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2024-09-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing permanent magnets have poor demagnetization at high temperatures and are highly dependent on rare earth materials, resulting in increased costs.

Method used

By polishing hard magnetic particles, their magnetic coercivity is improved and permanent magnets including polishing hard magnetic particles are formed to reduce dependence on rare earth materials.

Benefits of technology

It improves the anti-demagnetization of permanent magnets at high temperatures, reduces costs, and provides a wider range of application scenarios, such as motors in cold environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724892A_ABST
    Figure CN119724892A_ABST
Patent Text Reader

Abstract

A method for treating a magnetic material is provided. The method includes providing hard magnetic particles; the magnetic coercivity of the hard magnetic particles is improved by polishing the hard magnetic particles; and forming a permanent magnet, the permanent magnet comprising the polished hard magnetic particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the development of magnetic materials for magnets and magnets for electric motors. Background Art

[0002] Permanent magnets are formed from hard magnetic materials that retain their magnetism after being magnetized and are less susceptible to demagnetization than soft magnetic materials. Among the typical permanent magnet materials, ferrite and Nd-Fe-B (Neo) dominate the market: of the two materials, ferrite permanent magnet materials are lower in cost, while Neo permanent magnet materials have better performance. One factor in the implementation of permanent magnets in motors is demagnetization, which is (usually) achieved through their inherent coercivity H CJ To compensate for the temperature effect on magnetic properties (e.g. at high temperatures), an example strategy (e.g., an industrially applicable strategy) is to add dysprosium (Dy) or terbium (Tb) to Neo permanent magnets: Dy2Fe 14 B and Tb2Fe 14 The B phase shows a higher 14 BHigher magnetocrystalline anisotropy H A , which makes the permanent magnet have a higher H at all temperatures CJ , enabling potential implementation under harsh conditions. Enhanced H for some ferrite magnets CJ Another strategy uses chemical additives. All of the situations noted will affect the final cost. Summary of the invention

[0003] In a first aspect of the present disclosure, a method for processing magnetic materials is provided, which comprises providing hard magnetic particles; improving the magnetic coercivity of the hard magnetic particles by polishing the hard magnetic particles; and forming a permanent magnet comprising the polished hard magnetic particles.

[0004] In a second aspect according to the first aspect, providing hard magnetic particles further includes providing manganese-bismuth (Mn—Bi) alloy particles in a powder form.

[0005] In a third aspect according to the first and / or second aspect, the polished hard magnetic particles further include: mechanically polishing the hard magnetic particles using a polishing container; and removing the polished hard magnetic particles from the polishing container while exposing the polished hard magnetic particles to controlled environmental conditions.

[0006] In a fourth aspect according to any one of the first to third aspects, mechanically polishing the hard magnetic particles further includes mechanically polishing the hard magnetic particles by utilizing a frictional force between at least two of the hard magnetic particles.

[0007] In a fifth aspect according to any one of the first to fourth aspects, mechanically polishing the hard magnetic particles further includes mechanically polishing the hard magnetic particles by utilizing a friction force exerted on the hard magnetic particles by a surface of the polishing container.

[0008] In a sixth aspect according to any one of the first to fifth aspects, mechanically polishing the hard magnetic particles using the polishing container further comprises: providing a free polishing structure in the polishing container.

[0009] In a seventh aspect according to any one of the first to sixth aspects, mechanically polishing the hard magnetic particles using the polishing container further comprises: operating a speed of the polishing container based on the particle size and / or hardness of the hard magnetic material.

[0010] In an eighth aspect according to any one of the first to seventh aspects, mechanically polishing the hard magnetic particles using the polishing container further comprises operating a speed of the polishing container based on a spatial size of a portion of the container interacting with the hard magnetic particles.

[0011] In a ninth aspect according to any one of the first to eighth aspects, forming the permanent magnet further comprises: bonding the polished hard magnetic material to a polymer matrix while magnetically orienting the hard magnetic material.

[0012] In a tenth aspect according to any one of the first to ninth aspects, the method further comprises molding the polished hard magnetic material coupled to the polymer matrix by compression molding, transfer molding or injection molding.

[0013] In an eleventh aspect according to any one of the first to tenth aspects, forming the permanent magnet further comprises: densifying the polished hard magnetic material by sintering the polished hard magnetic material at a temperature higher than 200°C.

[0014] In a twelfth aspect according to any one of the first to eleventh aspects, improving the magnetic coercivity of the hard magnetic particles by polishing the hard magnetic particles further includes: improving the magnetic anisotropy of the hard magnetic particles by polishing the hard magnetic particles.

[0015] In a thirteenth aspect according to any one of the first to twelfth aspects, providing hard magnetic particles further comprises providing hard magnetic particles in liquid form, and wherein polishing the hard magnetic particles further comprises atomizing the liquid hard magnetic particles by exposing the stream of liquid hard magnetic particles to an atomizing force.

[0016] In a fourteenth aspect of the present disclosure, a permanent magnet is provided. The permanent magnet includes polished hard magnetic particles. A plurality of polished hard magnetic particles include a rounded surface along the periphery of a cross section of the polished hard magnetic particles.

[0017] In a fifteenth aspect according to the fourteenth aspect, the permanent magnet further comprises a polymer matrix bonded to the polished hard magnetic particles.

[0018] In a sixteenth aspect according to the fourteenth and / or fifteenth aspect, the polished hard magnetic particles include Mn—Bi alloy particles.

[0019] In a seventeenth aspect according to any one of the fourteenth to sixteenth aspects, the polished hard magnetic particles include densified polished hard magnetic particles.

[0020] In an eighteenth aspect of the present disclosure, an electric motor is provided, comprising a rotor, a stator, and a permanent magnet, the permanent magnet comprising polished hard magnetic particles, wherein a plurality of the polished hard magnetic particles comprise a circular surface along the periphery of a cross section of the polished hard magnetic particles.

[0021] In a nineteenth aspect according to the eighteenth aspect, the permanent magnet further comprises a polymer matrix bonded to the polished hard magnetic particles.

[0022] In a twentieth aspect according to the eighteenth and / or nineteenth aspect, the polished hard magnetic particles include Mn—Bi alloy particles.

[0023] The present disclosure also provides other aspects of the present disclosure, and any one of the first to twentieth aspects may be combined with any other features of the present disclosure disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The subject matter of the present disclosure will be described in more detail below based on exemplary drawings. All features described and / or shown herein may be used alone or in combination in different combinations. The features and advantages of various embodiments will become apparent by reading the following detailed description with reference to the accompanying drawings, which show the following:

[0025] Figure 1 A comparison of different J×H curves of different permanent magnets obtained at room temperature is shown;

[0026] Figure 2 The effect of temperature on the J×H curve and magnetic properties of Mn-Bi permanent magnets is shown;

[0027] Figure 3A An example of the particle geometry of a soft magnetic material before smoothing is shown;

[0028] Figure 3B shows an example of the particle geometry of the soft magnetic material after smoothing;

[0029] Figure 3C depicts an example of the particle geometry of a hard magnetic material after a smoothing process;

[0030] Figure 4 An example process for polishing hard magnetic particles is shown; and

[0031] Figure 5 An example of a cross section of an electric motor comprising permanent magnets is shown. DETAILED DESCRIPTION

[0032] Various aspects of the present disclosure provide many advantages. For example, smoothing of magnetic materials can reduce defects (concentration) of magnetic particles, thereby supporting the enhancement of the inherent coercivity of magnetic materials (e.g., hard magnetic materials). In addition, by enhancing the inherent coercivity of magnetic materials, a more diverse set of materials for manufacturing magnets (e.g., permanent magnets) can be considered, thereby reducing the dependence on rare earth materials and their associated costs. In addition, a variety of processes can be used to obtain smooth magnetic materials, thereby allowing flexible implementation suitable for various environments and uses.

[0033] The inventors of the present disclosure recognized that it is industrially interesting to utilize materials that can achieve higher intrinsic coercivity while maintaining affordable costs and avoiding the use of expensive elements (e.g., rare earth elements such as Nd, Dy, and Tb). These conditions can be met using Mn-Bi based permanent magnets. Various aspects of the present disclosure also provide improvements in Mn-Bi as a magnetic material (e.g., for permanent magnets). Enhancing the intrinsic coercivity of Mn-Bi can provide resistance to demagnetization at colder temperatures, thereby allowing more diverse applications of Mn-Bi permanent magnets (e.g., motors used in cold environments).

[0034] The examples of the disclosure presented will now be described more fully below with reference to the accompanying drawings, in which some, but not all, example embodiments of various aspects of the disclosure are shown. In fact, the embodiments performed according to various aspects of the disclosure may be illustrated in different forms and should not be construed as being limited to the examples set forth herein; on the contrary, these examples are provided to help fully understand the disclosure. Where possible, any term expressed in the singular herein is intended to also include the plural form, and vice versa, unless otherwise expressly stated. In addition, as used herein, the terms "one" and / or "an" shall mean "one or more", even if the phrase "one or more" is also used herein. In addition, when it is mentioned in this article that something is "based on" other things, it may also be based on one or more other things. In other words, unless otherwise expressly stated, as used herein, "based on" means "based at least in part on" or "based at least in part on".

[0035] The resistance of a material to demagnetization (eg, material coercivity) can be quantified by the applied magnetic field required to demagnetize the material (eg, reduce magnetic field B to zero). Materials can also have different magnetic properties (eg, different degrees of coercivity) depending on the degree of crystallographic alignment.

[0036] The magnetic properties of a material can be measured by the relationship between the material's magnetic polarization intensity J and the external magnetic field intensity H. For example, when the material's magnetic polarization intensity J is 0, the corresponding magnetic field intensity is called the intrinsic coercivity H. CJ The intrinsic coercivity of the material H CJ The strength of reflects the anti-demagnetization strength of the magnetic material. Apply an external magnetic field exceeding the material tolerance to the reverse magnetic field H k (e.g. knee coercivity and / or knee field) may induce demagnetization (e.g. applying a field where the polarization J is reduced to 90% of the remanence of the permanent magnet). k With H CJ The relationship between (e.g., perpendicularity) can provide information about the stability of the permanent magnet under dynamic operating conditions.

[0037] Figure 1 Graph 100 provides examples of J×H curves for four different and distinct magnetic materials obtained at approximately room temperature, wherein each curve indicates the relationship between the corresponding magnetic material polarization intensity J and the external magnetic field H, wherein the intrinsic coercivity H of each material is CJ It is shown at J = 0. The external magnetic field strength H is shown along the x-axis, measured in kA / m, and the magnetic polarization strength J is shown along the y-axis, measured in Tesla.

[0038] In addition to the graph 100, other magnetic properties are provided for different and distinct magnetic materials, such as the remanence B r (A measure of the residual magnetic induction or flux density in a magnet after magnetization (e.g., the resulting strength of a permanent magnet)).

[0039] Curve 102 depicts the magnetic properties of an example of a bonded Sm-Fe-N magnet (e.g., a magnet comprising and / or made of a polymer bonded Sm-Fe-N magnetic material) at 26°C, wherein H CJ The value is 784 kA / m. Curve 106 depicts the magnetic properties of an example of a bonded ferrite magnet (e.g., a magnet comprising and / or made of a polymer bonded ferrite magnetic material) at 27°C, with H CJ The value is 375 kA / m. Curve 108 depicts the magnetic properties of an example of a sintered ferrite magnet (e.g., a magnet comprising and / or made of a sintered ferrite magnetic material) at 20°C, wherein H CJ The value is 318kA / m.

[0040] Curve 104 depicts the magnetic properties of an example of a bonded unpolished Mn-Bi magnet (e.g., a magnet comprising and / or made of a polymer bonded Mn-Bi magnetic material) at 23°C. The bonded unpolished Mn-Bi magnet has the following magnetic properties: r The value is .352T, H CB The value is 266kA / m, H CJ The value is 773kA / m, (BH) max The value is 24kJ / m 3 , J k The value is .317T, H k The value is 386kA / m, and H D5 The value is 599kA / m.

[0041] Mn-Bi permanent magnetic materials in powder form (such as raw materials for permanent magnet manufacturing) can have a remanence B at room temperature. r =0.70T and H CJ = 1.20 T. However, once the powder is sintered (e.g., densified in the final shape), the intrinsic coercivity may decrease (e.g., H CJ <0.50T). This decrease may be due to the increased defects during compaction (Wei Tang et al., Engineering microstructure to improve coercivity of bulk MnBi magnet, 563 Journal of Magnetism and Magnetic Materials (2022)). On the other hand, when Mn-Bi permanent magnets are manufactured in a combined form (e.g., powder mixed with a binder), the remanence B r The remanence B of a sintered ferrite (such as the sintered ferrite shown by curve 108) can be close to r , and the intrinsic coercivity H CJ It can reach between 0.95T and 1.20T, such as Figure 1 As shown in curve 104 (e.g., the bonded unpolished Mn-Bi magnet shown in curve 104). As shown in curve 104, Mn-Bi in powder form has good resistance (e.g., H CJ ), about three times that of ferrite.

[0042] Figure 2 The graph 200 provides examples of J×H curves of Mn—Bi bonded permanent magnets obtained at different temperatures, and thus illustrates the effect of temperature on the J×H curves, and the magnetic properties and performance of the Mn—Bi permanent magnets. Figure 1As shown, the external magnetic field strength H is shown in kA / m along the x-axis, and the magnetic polarization strength J is shown in Tesla along the y-axis.

[0043] Curve 202 depicts the magnetic properties of an example bonded (e.g., polymer bonded) Mn-Bi permanent magnet (e.g., a magnet including and / or made of bonded Mn-Bi magnetic material) at 82°C. The example bonded Mn-Bi magnet has the following magnetic properties: r The value is .308T, H CB The value is 225kA / m, H CJ The value is 955kA / m, (BH) max The value is 18kJ / m 3 , J k The value is .278T, H k The value is 268kA / m, and H D5 The value is 804kA / m.

[0044] Curve 204 depicts the magnetic properties of an example bonded (e.g., polymer bonded) Mn-Bi permanent magnet (e.g., a magnet including and / or made of bonded Mn-Bi magnetic material) at 26°C. The example bonded Mn-Bi magnet has the following magnetic properties: r The value is .335T, H CB The value is 251kA / m, H CJ The value is 771kA / m, (BH) max The value is 21kJ / m 3 , J k The value is .301T, H k The value is 356kA / m, and H D5 The value is 593kA / m.

[0045] Curves 202 and 204 show the intrinsic coercivity H of an example bonded Mn—Bi permanent magnet. CJ In fact, it increases with increasing temperature and can be greater than rare earth materials and Figure 1 The curve of performs better (e.g., at least in part due to the positive coercivity coefficient). However, as the temperature decreases (e.g., when the Mn—Bi permanent magnet is deployed as part of a traction motor in a cold environment), the intrinsic coercivity H CJmay be proportionally smaller. Thus, while some hard magnetic materials such as unpolished Mn-Bi may exhibit advantages at elevated temperatures (e.g., during operation, in applications requiring power density, or potentially, in warm climates), these materials may face challenges in deployment in climates such as Canada or Russia, or potentially, even as traction motors in cold storage facilities where the starting temperatures may be very low. In contrast, the inherent coercivity H of materials such as Neo-based chemistries is CJ Increased resistance may be exhibited at lower temperatures, and decreased resistance may be exhibited at elevated temperatures.

[0046] Thus, the inventors of the present invention have recognized that enhancing the coercivity of some hard magnetic materials such as Mn-Bi (e.g., at low temperatures) can provide a number of advantages. For example, the combined Mn-Bi appears to be very suitable for traction applications in magnet-assisted methods. For example, considering the B of a Mn-Bi magnetic material that can provide a suitable weak magnetic capability, r Limited, when operating at high speed and low torque level, Mn-Bi can allow greater power at higher speed and lower losses. Mn-Bi magnetic materials can also provide resistance to demagnetization and demagnetization during low speed and high torque.

[0047] The inventors of the present invention have also recognized that for hard magnetic materials such as Mn-Bi, the strong intrinsic coercivity H CJ Permanent magnets may be advantageous because of the strong intrinsic coercivity H CJ It can reflect the resistance of permanent magnets to demagnetization. For example, for permanent magnets deployed in electric motors, the demagnetization of permanent magnets may cause motor failure or damage. Therefore, enhancing the intrinsic coercivity H of hard magnetic materials CJ It can provide many advantages in different deployments, such as increasing the difficulty of demagnetization (e.g., increasing the strength of the applied magnetic field to demagnetize the soft magnetic material), improving stability and reliability under different dynamic conditions (e.g., deployment temperature, power requirements). CJ Permanent magnets may be advantageous because in a given implementation, it may be necessary to magnetize and demagnetize the soft magnetic material. For example, an electric motor lamination may include a soft magnetic material that is designed to change polarity when rotated around the magnetic field of a permanent magnet or electromagnet. Thus, the inherent coercivity H of the soft magnetic material is reduced. CJ Many advantages may be provided, such as improving stability and reliability under different dynamic conditions by making magnetization and demagnetization easier (eg, reducing the strength required to apply a magnetic field to demagnetize a soft magnetic material).

[0048] The soft magnetic material (e.g. in powder form, corresponding to the magnetic core) can be as Figure 3A and Figure 3B As shown, the powder particles may be smoothed to improve their respective properties for a given embodiment. This may be achieved, for example, by smoothing (e.g., polishing) the surface of the powder particles (e.g., changing the geometry of the soft magnetic particles). For example, Figure 3A and Figure 3B As shown, Figure 3A The unpolished Ni-Fe-Mo alloy material shown in views 300 and 302 of the drawings can be smoothed (e.g., polished) by mechanical processing (e.g., ball milling) to produce Figure 3B 304 and 306 of a Ni-Fe-Mo alloy material grain, wherein the grain exhibits one or more polished surfaces. Although polishing produces an irregular, multi-sided geometry of the grain as shown in view 304, polishing may also produce a smoother, more rounded geometry as shown in view 306. Figure 3B The mechanically polished particles in the alloy exhibit increased magnetic permeability (e.g., 300% increase), as well as the inherent coercivity H resisted by the alloy material. CJ Resulting in reduced losses and other magnetic losses (e.g., a reduction of at least 35%). This improvement in the ease of magnetization and demagnetization of soft magnetic materials (e.g., reduction in magnetic losses) can be at least partially attributed to mechanical polishing, because mechanical polishing eliminates obstacles and defects that hinder the displacement of magnetic domain walls and increases magnetic anisotropy.

[0049] For some hard magnetic materials (e.g., Neo, ferrites), the elimination of some defects (e.g., pores, stress relief) can occur during the densification (e.g., sintering) process. However, due to the low sintering (e.g., densification) temperature of the magnetic material (e.g., for Mn-Bi < 300°C) related to the decomposition temperature of the hard magnetic phase (e.g., the temperature that causes the magnetic properties and magnetic resistance of the Mn-Bi magnetic material to decrease), other hard magnetic materials (e.g., Mn-Bi) may not be able to reach a suitable defect reduction temperature level. Therefore, the inventors of the present invention have recognized that improving the performance of hard powder magnetic materials (e.g., Mn-Bi permanent magnet materials) can provide a method for enhancing (e.g., increasing and / or improving) the demagnetization resistance of Mn-Bi. For example, defects that reduce (local) magnetic anisotropy (e.g., inclusions, corners) are eliminated to support the enhancement of the intrinsic coercivity of hard magnetic particles (e.g., Mn-Bi magnetic materials) and magnets.

[0050] Therefore, polishing (e.g., smoothing) such as Figure 3A and Figure 3B The soft magnetic material in the can make the material easier to magnetize and demagnetize, while in contrast to the soft magnetic material, polishing the hard magnetic material (e.g. Figure 3C As shown) can make Mn-Bi less prone to magnetization and demagnetization.

[0051] Figure 4An example process 400 for polishing hard magnetic material and making permanent magnets using the polished hard magnetic material is provided. For example, the process 400 may use a coarse unpolished particle such as Figure 3C Particle 308 is shown in cross section, and a polished particle (e.g., particle 310, 312, or 314, also shown in cross section) is produced that exhibits an improved reduction in local magnetic anisotropy effects. The polished particle 310, 312, or 314 can then be used to produce a permanent magnet (e.g., by sintering or bonding the polished particles 310, 312, or 314). The following steps are examples of how to perform process 400, and can be performed separately (e.g., performing only steps 402 and 404, or 402 to 406, to produce a polished hard magnetic material) or performed together (e.g., performing steps 402, 404, and 410, or 402 to 410, to form a permanent magnet).

[0052] Step 402 includes providing hard magnetic particles. For example, providing hard magnetic particles and / or (e.g., particles 308) can be provided in powder form (e.g., alloy powder). The powder form of these particles can be obtained, for example, by crushing the material produced by casting (e.g., including heat treatment) and melt spinning of the initial elements, wherein the melt spinning uses a wheel to spin the hard magnetic material in molten liquid form. For example, the hard magnetic particles (e.g., particles 308) can be an alloy in the form of Mn-Bi powder. The hard magnetic particles can also be provided in liquid form (e.g., molten Mn-Bi), and step 404 can be directly applied to the molten Mn-Bi particles in liquid form.

[0053] Particles 308 may have a variety of geometries, either regular or irregular, and may include a number of rough and irregular surfaces (e.g., surface irregularities 316). These irregular (e.g., abnormal, rough) surfaces may be the result of the formation of a powder form during the intrinsic crystal formation process of the hard magnetic material (e.g., when in an imperfect liquid form such as molten Mn-Bi), or a previous process to form particles 308 (e.g., mechanical grinding or powderization of a larger Mn-Bi mass).

[0054] Step 404 includes improving the magnetic coercivity of the hard magnetic particles by polishing the hard magnetic particles. For example, the particles 308 can be smoothed (e.g., polished) and are similar to any of the particles 310, 312, and / or 314. The polished particles 312 exhibit a perfectly continuous circular surface 318 (e.g., along the periphery of a cross section of a sphere or cylinder) and can exhibit greatly improved magnetic coercivity (e.g., a very uniform domain wall displacement effect of the hard magnetic material) compared to the unpolished particles 308. However, due to possible manufacturing limitations, a perfectly continuous circular surface of the entire particle 312 may not always be feasible. However, the polished particles 310 have surfaces 320 that together form at least substantially continuous circular surfaces 322. In addition, although the substantially continuous circular surface 322 is shown as being formed by the surface 320, due to the polishing of the particles 308, the surface 324 can also constitute (e.g., provide) a continuous circular surface 322. Polished particle 314 also has surface 326 that resembles a flatter surface (e.g., similar to a disk) than surface 318 or 310 in terms of a more continuous percentage of the size of particle 314. For example, polishing of particle 314 may occur primarily in one or two axes of motion, while polishing of particles 310 and 312 may occur in three axes. However, surface 326 provides polished surfaces that may collectively form at least substantially continuous rounded surface 328.

[0055] As shown by particle 314, the polished surface or polished cross-section of the particle does not have to be symmetrical; as long as a polished surface is present, at least some improvement in the magnetic coercivity described above can be expected. For example, one way to achieve enhanced intrinsic coercivity is to increase the magnetic anisotropy of the hard magnetic particles. This can be achieved by polishing the hard magnetic particles.

[0056] Step 404 can be performed according to a plurality of polishing processes. For example, the particles (e.g., any of particles 308, 310, 312, and / or 314) can be smoothed by themselves (e.g., by the surface 316 of one particle interacting with the surface 316 of another different particle in contact, or by mechanical friction caused by the surface 320 interacting with other surfaces 316, 320, 324, 326). In other words, mechanical polishing of the hard magnetic particles can be performed by using friction applied by a first hard magnetic particle in the hard magnetic particles to a second hard magnetic particle in the hard magnetic particles. Chemical polishing (e.g., a polishing material that induces controlled erosion) can also be used alone or in combination with other mechanical polishing methods to polish the particles.

[0057] Another form of polishing can be performed using a polishing container. For example, when step 406 is performed, step 406 includes mechanically polishing the hard magnetic particles using a polishing container. For example, the container can be rotated to polish the hard magnetic particles in the container. The rotation can occur at a controlled or predetermined speed based on the physical parameters of the specific powder (e.g., particle size, hardness, total kilograms of powder in the container) and / or the parameters of the container (e.g., geometry, circumference, diameter). Therefore, the speed of the polishing container can be operated to mechanically polish the hard magnetic particles based on the physical parameters of the hard magnetic material and / or based on the spatial dimensions of the portion of the container that interacts with the hard magnetic particles. During the polishing process, the forces (e.g., friction, corrosion) present between the Mn-Bi particles and the grinding surface of the container can shape the powder into a smooth "finished product", making the particle surface rounded, thereby helping to avoid demagnetization in low magnetic fields and improving its magnetic properties.

[0058] Polishing can provide a variety of different types of polishing. For example, the polishing container can include a grinding liner for polishing hard magnetic materials. In other words, the hard magnetic particles can be mechanically polished using friction forces applied by the surface of the polishing container on the first hard magnetic particles in the hard magnetic particles. Polishing can also include a free (e.g., non-fixed) polishing structure that operates within the container to rotate with the powder and polish the powder (e.g., ball milling). In other words, by providing a free polishing structure within the polishing container, the hard magnetic particles can be mechanically polished using the polishing container.

[0059] Another form of polishing is atomization. For example, when the hard magnetic material is provided in a molten form, the molten material can be exposed to an atomizing force to produce polished particles (e.g., particles 310, 312, 314). For example, an air stream or a liquid stream can be applied to the molten hard magnetic material as an atomizing force, wherein droplets are pulled away from the top of the molten material by the air or liquid stream and collected. The droplets collected by these locks can then resemble magnetic particles with a polished surface. In other words, the hard magnetic particles can be polished by exposing the liquid hard magnetic particle stream to an atomizing force to atomize the liquid hard magnetic particles.

[0060] When step 408 is performed, step 408 includes removing the polished hard magnetic particles from the polishing container while exposing the polished hard magnetic particles to controlled environmental conditions. For example, the polished hard magnetic particles (e.g., particles 310, 312, 314) can be removed from the container in the presence of an inert controlled atmosphere to prevent chemical reactions that may cause the polished particles to become uneven (e.g., cause surface defects). For example, the polished particles can be removed from the polishing container without being exposed to an environment where oxygen and / or moisture are present.

[0061] Step 410 includes forming a permanent magnet comprising polished hard magnetic particles. For example, the polished hard magnetic particles can be used in combination with other processes or materials to form a permanent magnet with improved magnetic coercivity of the polished hard magnetic material. Two examples include permanent magnets prepared with sintered or bonded polished hard magnetic materials, and can include magnetic alignment (e.g., orientation) of the material during bonding or sintering. For sintered (e.g., densified) hard magnetic materials (e.g., Mn-Bi), the material can be compacted to form a permanent magnet of a specific geometry and densified under controlled time, temperature, and / or atmosphere procedures. For bonding, the hard magnetic material (e.g., Mn-Bi) can be mixed and coupled with a binder, such as an inorganic, organic (e.g., from a thermosetting plastic and / or thermoplastic family) or a polymer matrix of a mixture of the two, and densified by industrially available processes, including compression molding, transfer molding, or injection molding. At least one advantage of a polymer binder is that for certain hard magnetic materials that are magnetically sensitive to the range of heat and pressure required to perform densification, the bonding process can be used to avoid exposing the material to the heat and pressure of the densification process. The resulting permanent magnet can then be used in a variety of different applications while exhibiting improved magnetic coercivity and resistance to demagnetization caused by polished hard magnetic particles.

[0062] Aspects of the present invention may also provide for the development of magnetic materials for permanent magnet motors, such as permanent magnet motor 500. For example, electric motor 500 includes stator 502, rotor 504, shaft 506, permanent magnets 508, and stator windings 510. When permanent magnets 508 are disposed outside rotor 504 (e.g., within stator 502, shown by dashed lines to indicate optional use), motor 500 may be a surface permanent magnet motor. When permanent magnets 508 are disposed inside rotor 504, motor 500 may be an internal permanent magnet motor. By implementing permanent magnets 508 in an industrial electric motor, such as electric motor 500, the permanent magnets may help generate (e.g., facilitate generation of) a constant magnetic density flux in motor 500.

[0063] For example, the stator 502 and the rotor 504 can be magnetically coupled to each other (e.g., magnetically connected to each other, magnetically / electrically interacting with each other). The stator 502 can include stator windings 510, which can carry charges caused by the rotation of the permanent magnets 508 in the rotor 504, or can generate magnetic flux by applying current to the stator windings 510, causing the rotation of the rotor 504. For example, by selectively applying power to different (e.g., consecutive) stator windings 510 in the rotation direction, the stator windings 510 can help drive the permanent magnets 508 in the rotor 504 in a synchronous phase, thereby forming a permanent magnet assisted synchronous reluctance motor.

[0064] The shaft 506 may be fixed to the rotor 504 and transmit the rotational force applied to the rotor 504 to the corresponding components as mechanical power. Alternatively, the shaft 506 may also transmit the rotational force to the rotor 504 to rotate the rotor 504 and promote the generation of electricity through the stator winding 510 of the electric motor 500.

[0065] In some cases, a particular motor topology may be more or less dependent on the flux of the permanent magnets used to produce torque, and it may be desirable to adjust (e.g., increase or decrease) the flux for a specific implementation of the motor. One case involves a permanent magnet assisted synchronous reluctance motor in which the torque is due in part to the anisotropy of the soft magnetic laminations implemented in the rotor. In some examples, providing a magnetic material that is resistant to demagnetization (especially at elevated temperatures) and / or has a flux density and cost comparable to sintered ferrites compared to or superior to Neo grades without added Tb and Dy (e.g., polished magnetic materials produced according to one or more embodiments of the present invention) can help address industry issues (e.g., the techno-economic gap between the two main hard magnetic compounds).

[0066] In some examples, a permanent magnet motor may be implemented to provide and / or assist in the movement and / or propulsion of a vehicle (e.g., a traction motor). In some cases, the traction motor may be subject to high temperatures, high temperature variations, and thermal stresses. Because many magnetic materials have a high relative humidity, the magnetic field may be very large. CJ Has a negative temperature coefficient, so increase the H of the permanent magnet and / or permanent magnet material CJ A more efficient and reliable electric motor may be provided.

[0067] Permanent magnets produced by polishing hard magnetic materials (such as Mn-Bi materials) can be advantageously used in industrial machines and possibly traction motors (considering H CJ traction motors). For example, rare earth elements are not necessarily used in the composition of permanent magnets, thereby reducing supply chain constraints on key materials controlled by a single economic source. Permanent magnets can also provide manufacturing flexibility because hard magnetic materials can be developed in different production processes, including compression molding, transfer molding, injection molding (which can utilize binders), and sintering (which does not require binders). In some cases, the smoothing process produces more rounded particles, which facilitates the mixing process of the powder with the selected binder (which can include thermosetting and / or thermoplastic compounds).

[0068] Although the subject matter of the present disclosure has been illustrated and described in detail in the drawings and the foregoing description, such illustration and description should be considered illustrative or exemplary rather than restrictive. Any statements made herein describing features of the present invention should also be considered illustrative or exemplary rather than restrictive, as the present invention is defined by the claims. However, it should be understood that changes and modifications may be made by one of ordinary skill in the art within the scope of the appended claims, which may include any combination of features from the different embodiments described above.

[0069] The terms used in the claims should be interpreted as having the widest reasonable interpretation consistent with the foregoing description. For example, the use of the article "one" or "the" when introducing an element should not be interpreted as excluding multiple elements. Similarly, the narration of "or" should be interpreted as inclusive, so that the narration of "A or B" does not exclude "A and B", unless it is clear from the context or the foregoing description that only one of A and B is intended to be indicated. In addition, the narration of "at least one of A, B and C" should be interpreted as one or more of a group of elements consisting of A, B and C, and should not be interpreted as requiring at least one of each of the listed elements A, B and C, regardless of whether A, B and C are related as categories or otherwise. In addition, the narration of "A, B and / or C" or "at least one of A, B or C" should be interpreted as including any singular entity from the listed elements, such as A, from any subset of the listed elements, such as A and B, or the entire list of elements A, B and C.

Claims

1. A method for processing a magnetic material, the method comprising: providing hard magnetic particles; improving the magnetic coercivity of the hard magnetic particles by polishing the hard magnetic particles; as well as A permanent magnet is formed, the permanent magnet comprising polished hard magnetic particles.

2. The method of claim 1, wherein providing the hard magnetic particles further comprises: Manganese-bismuth (Mn—Bi) alloy particles are provided in powder form.

3. The method of claim 1, wherein polishing the hard magnetic particles further comprises: mechanically polishing the hard magnetic particles using a polishing container; as well as The polished hard magnetic particles are removed from the polishing container while being exposed to controlled environmental conditions.

4. The method of claim 3, wherein mechanically polishing the hard magnetic particles further comprises: The hard magnetic particles are mechanically polished by utilizing friction between at least two of the hard magnetic particles.

5. The method of claim 3, wherein mechanically polishing the hard magnetic particles further comprises: The hard magnetic particles are mechanically polished by utilizing a friction force applied to the hard magnetic particles by the surface of the polishing container.

6. The method of claim 3, wherein mechanically polishing the hard magnetic particles using a polishing container further comprises: A free polishing structure is provided within the polishing container.

7. The method of claim 3, wherein mechanically polishing the hard magnetic particles using a polishing container further comprises: The speed of the polishing container is operated based on the particle size and / or hardness of the hard magnetic material.

8. The method of claim 3, wherein mechanically polishing the hard magnetic particles using a polishing container further comprises: The speed of the polishing container is operated based on the spatial dimensions of the portion of the container that interacts with the hard magnetic particles.

9. The method of claim 1 , wherein forming the permanent magnet further comprises: The polished hard magnetic material is bonded to a polymer matrix while magnetically orienting the hard magnetic material.

10. The method according to claim 9, further comprising: The polished hard magnetic material coupled to a polymer matrix is ​​molded by compression molding, transfer molding or injection molding.

11. The method of claim 1 , wherein forming the permanent magnet further comprises: The polished hard magnetic material is densified by sintering the polished hard magnetic material at a temperature above 300°C.

12. The method of claim 1, wherein improving the magnetic coercivity of the hard magnetic particles by polishing the hard magnetic particles further comprises: By polishing the hard magnetic particles, the magnetic anisotropy of the hard magnetic particles is increased.

13. The method of claim 1, wherein providing the hard magnetic particles further comprises: Providing the hard magnetic particles in liquid form, and wherein polishing the hard magnetic particles further comprises: The hard magnetic particles of liquid are atomized by exposing the stream of the hard magnetic particles of liquid to an atomizing force.

14. A permanent magnet, comprising: Polished hard magnetic particles, wherein a plurality of the polished hard magnetic particles include a rounded surface along a perimeter of a cross-section of the polished hard magnetic particles.

15. The permanent magnet according to claim 14, further comprising: A polymer matrix is ​​bonded to the polished hard magnetic particles.

16. The permanent magnet of claim 14, wherein the polished hard magnetic particles comprise Mn-Bi alloy particles.

17. The permanent magnet of claim 14, wherein the polished hard magnetic particles comprise densified polished hard magnetic particles.

18. An electric motor, comprising: Rotor; stator; as well as A permanent magnet comprising polished hard magnetic particles, wherein a plurality of the polished hard magnetic particles comprise a rounded surface along a perimeter of a cross section of the polished hard magnetic particles.

19. The electric motor of claim 18, wherein the permanent magnet further comprises: A polymer matrix is ​​bonded to the polished hard magnetic particles.

20. The electric motor of claim 18, wherein the polished hard magnetic particles comprise Mn-Bi alloy particles.